PENUMBUHAN MINAT BACA PESERTA DIDIK PENDIDIKAN MULTIKEAKSARAAN MELALUI CERITA RAKYAT SUKU SASAK [INCREASING READING INTEREST OF STUDENTS IN MULTICULTURAL EDUCATION THROUGH SASAKNESE FOLKLORE] - IRHAM YUDHA PERMANA; Dani Soraya; Mokhamad Romadoni (Jurnal AKRAB, 2019)
The research aims to describe the readability of the procedural script, the readability of the learning curriculum, the readability of teaching materials of Sasaknase folklore books, the effectiveness of the script implementation, and the effectiveness of increasing reading interest of the students through Sasaknese folklore to their literacy understanding. It is conducted by using quantitative and qualitative approaches. Data analysis is carried out by employing descriptive and t-test analysis. The result of the research shows that there is a significant influence of the growing interest in reading through Sasaknese folklore towards students’ literacy enhancement.